PENGARUH POSISI SHIELDED METAL ARC WELDING (SMAW) GERAK SPIRAL KAMPUH V TERHADAP KEKUATAN TARIK DAN STRUKTUR MIKRO BAJA KARBON RENDAH - Ahmadi, Nurfi; Nugroho, Fajar; Ahmad A, Dadang (Institut Teknologi Dirgantara Adisutjipto, 2023)
The purpose of this study was to determine the relationship between the position of shielded metal arc welding (SMAW) with spiral motion V on the tensile strength and microstructure of low carbon steel. The research was conducted by welding V-coated low carbon steel with horizontal 2G, vertical 3G and overhead 4G. The test results show that the welding position does not have a significant effect on the tensile strength of low carbon steel welds, where the 3G vertical position provides a higher tensile strength value than the 2G horizontal position and 4G overhead. The microstructure of acicular ferrite (AF) in the vertical position looks dominant uniformly and tightly.